PENGARUH KETEPATAN PEMILIHAN METODE MENGAJAR GURU DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI IIS SMA NEGERI 2 SIAK HULU - Andana, Suci; Gimin, Gimin; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the accuracy of the selection of teacher teaching methods and learning motivation of class XI IIS students of SMAN 2 Siak Hulu, and find out how much influence the selection of teacher teaching methods and learning motivation has on the learning outcomes of XI IIS students at SMAN 2 Siak Hulu. The research was conducted in November 2018. The population in this study were students of class XI IIS of SMAN 2 Saik Hulu which amounted to 189 students using the Proportional Random Sampling technique which took subjects from each strata or each region. Data collection techniques are carried out through observation, questionnaires, and documentation. The research method used is quantitative descriptive analysis. This method is done by processing the results data presented through the calculation of the percentage of the questionnaire.Based on the results of the analysis and discussion, the multiple linear regression equation is obtained Y = 53,758 + 0,205 (X1) + 0,274 (X2). Based on the test of the coefficient of determination (R2) the percentage of contributions contributed to the variable accuracy of the selection of teacher teaching methods and learning motivation towards the economic learning outcomes of class XI students of SMAN 2 Siak Hulu at 18.2%. It can be concluded that the accuracy of teacher teaching methods and learning motivation has a significant effect on the economic learning outcomes of class XI students of SMAN 2 Siak Hulu. Key Words: Learning Outcomes, Accuracy of Teaching Method Selection, Learning Motivation